Calcium fortification of tocino using calcium carbonate - Degayo, Anastacio Manuel Jun-jun Sulleza
This study was done primarily to develop a calcium-fortified Tocino and to assess the retention of clcium in the product after processing. Formulation by Claudio (1977) was fortified 33% of the Philippine RDA for calcium for 10 to 19 years old. The sensory properties were determined using descriptive and acceptability tests. Student's t-Test at α=0.05 showed the fortified Tocino is not significntly different from the control in most sensory properties. Physico-chemicl properties and calcium analysis of both the control an the fortified Tocino showed that the control sample has a pH of 5.6833 and 42.58% moisture content. The fortified sample has pH of 6.1000 and 40.88% moiture contnet. The elemental calcium retained in the fortified sample after processing was 93.71%. Cooking Yields indicated that 15.21% of the control was lossed during processing while the fortified sample has 1221% cooking loss.